2016
DOI: 10.1021/acssensors.6b00531
|View full text |Cite
|
Sign up to set email alerts
|

Response Monitoring of Acute Lymphoblastic Leukemia Patients Undergoing l-Asparaginase Therapy: Successes and Challenges Associated with Clinical Sample Analysis in Plasmonic Sensing

Abstract: Monitoring the response of patients undergoing chemotherapeutic treatments is of great importance to predict remission success, avoid adverse effects and thus, maximize the patients’ quality of life. In the case of leukemia patients treated with E. coli l-asparaginase, monitoring the immune response by the detection of specific antibodies to l-asparaginase in the serum of patients can prevent extended immune response to the drug. Here, we developed a surface plasmon resonance (SPR) biosensor to rapidly detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 44 publications
(63 reference statements)
0
27
0
Order By: Relevance
“…Although the His-tagged EcAII displayed lower sensing efficiency than the native EcAII, it provided increased surface coverage and reproducibility of immobilization, ultimately procuring significantly increased immunodetection sensitivity. These results shed light on the challenges encountered in our recently reported detection of serum anti-asparaginase antibodies in the sera of children undergoing chemotherapy 23 and the challenges expected to be encountered by others developing sensors to monitor the immunogenic response of patients undergoing therapy with biologic-type drugs.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although the His-tagged EcAII displayed lower sensing efficiency than the native EcAII, it provided increased surface coverage and reproducibility of immobilization, ultimately procuring significantly increased immunodetection sensitivity. These results shed light on the challenges encountered in our recently reported detection of serum anti-asparaginase antibodies in the sera of children undergoing chemotherapy 23 and the challenges expected to be encountered by others developing sensors to monitor the immunogenic response of patients undergoing therapy with biologic-type drugs.…”
Section: Introductionmentioning
confidence: 79%
“…Calibration of the sensor was performed with serial injections of increasing concentrations of anti-asparaginase antibodies on a single sensor chip, as previously described. 23 The SPR shifts were calculated with MATLAB software and served to calculate the surface density of the analyte bound onto the immobilized antigenic receptors, as described above. Taking into account the exact MW of each EcAII variant, we calculated the number of EcAII molecules immobilized on the sensing surface (molecule cm –2 ).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Hence, it was revealed that SPR and ECL are complementary and offer similar performances for the detection of antibodies . SPR sensors provide quantitative real‐time information on the adsorption of molecules to a surface, although the analysis of clinical samples in biofluids may be difficult . ECL provides high sensitivity, high selectivity, and low detection limits even in crude matrices as it is relatively insensitive to nonspecific adsorption of biofluids, but lacks information on the adsorption processes occurring on the electrode.…”
Section: Figurementioning
confidence: 99%
“…[3] SPR sensors provide quantitative real-time information on the adsorption of molecules to as urface,a lthough the analysis of clinical samples in biofluids may be difficult. [4] ECL provides high sensitivity,h igh selectivity,a nd low detection limits even in crude matrices as it is relatively insensitive to nonspecific adsorption of biofluids,b ut lacks information on the adsorption processes occurring on the electrode.H ence,t he combination of SPR and ECL in as ingle instrument would be beneficial to monitor interfacial processes involved in ECL and to design biosensors with improved performances. To fully benefit from the combination of the techniques, at horough understanding of the underlying principles is needed.…”
mentioning
confidence: 99%